Evidence of Male Hair Pencil Pheromone in Choristoneura fumiferana (Lepidoptera: Tortricidae). Issue 1 (4th March 2016) - Roscoe, Lucas E.; Silk, P.; Eveleigh, E. S.
Abstract: Male Lepidoptera often possess specialized scales, called hair pencils that emit volatiles that are critical to mating success. Spruce budworm, Choristoneura fumiferana (Clemens) (Lepidoptera: Tortricidae), males will display hair pencils to females before attempting copulation. The importance of volatiles on these hair pencils is, however, not clear. We compared the proportion of successful copulations in unmanipulated mating pairs to pairs where males had their hair pencils either removed or chemically washed, and to pairs where females were antennectomized. Mean proportions of successful matings were significantly lower in pairs where hair pencils had been manipulated or where females had been antennectomized compared with unmanipulated mating pairs. There was no significant difference in mating success between treatments where hair pencils had been manipulated; however, mating success was significantly lower in hair pencil treatments than in antennectomized treatments. Mean copulation proportions in hair pencil/antennectomized treatments were also significantly less than in respective sham-operated treatments. Our results suggest that volatiles are associated with hair pencils, and they may be required for mating success in C. fumiferana.